Liquid phase exfoliation of rubrene single crystals into nanorods and nanobelts - Rao, Vaishnavi J.; Qi, Haoyuan; Berger, Felix J.; Grieger, Sebastian; Kaiser, Ute; Backes, Claudia; Zaumseil, Jana (ACS nano, 2021)
Liquid phase exfoliation (LPE) is a popular method to create dispersions of two-dimensional nanosheets from layered inorganic van der Waals crystals. Here, it is applied to orthorhombic and triclinic single crystals of the organic semiconductor rubrene with only noncovalent interactions (mainly π-π) between the molecules. Distinct nanorods and nanobelts of rubrene are formed, stabilized against aggregation in aqueous sodium cholate solution, and isolated by liquid cascade centrifugation. Selected-area electron diffraction and Raman spectroscopy confirm the crystallinity of the rubrene nanorods and nanobelts while the optical properties (absorbance, photoluminescence) of the dispersions are similar to rubrene solutions due to their randomized orientations. The formation of these stable crystalline rubrene nanostructures with only a few molecular layers by LPE confirms that noncovalent interactions in molecular crystals can be strong enough to enable mechanical exfoliation similar to inorganic layered materials.